Creating an academic literacy framework to enhance collaboration between learning developers and subject academics - Rosella D'Alesio (Association for Learning Development in Higher Education (ALDinHE), 2019)
As learning developers, we are constantly engaging with subject lecturers to discuss the learning needs of our students. This case study describes the creation of an academic literacy framework designed to engage subject lecturers and improve collaboration between them and the learning development team in order to develop the academic skills of students. Our aim was to create a tool that would achieve three complementary goals: • Help subject lecturers pinpoint where their students are placed along a spectrum of skills. • Allow lecturers to request, and/or learning developers to recommend, skills sessions at the most appropriate time. • Allow the learning development team to identify gaps in provision.